Multiple systemic embolism in infective endocarditis underlying in Barlow's disease. Issue 1 (December 2016) - Yu, Ziqing; Fan, Bing; Wu, Hongyi; Wang, Xiangfei; Li, Chenguang; Xu, Rende; Su, Yangang; Ge, Junbo
Abstract Background Systemic embolism, especially septic embolism, is a severe complication of infective endocarditis (IE). However, concurrent embolism to the brain, coronary arteries, and spleen is very rare. Because of the risk of hemorrhage or visceral rupture, anticoagulants are recommended only if an indication is present, e.g. prosthetic valve. Antiplatelet therapy in IE is controversial, but theoretically, this therapy has the potential to prevent and treat thrombosis and embolism in IE. Unfortunately, clinical trial results have been inconclusive. Case presentation We describe a previously healthy 50-year-old man who presented with dysarthria secondary to bacterial endocarditis with multiple cerebral, coronary, splenic, and peripheral emboli; antibiotic therapy contributed to the multiple emboli. Emergency splenectomy was performed, with subsequent mitral valve repair. Pathological examination confirmed mucoid degeneration and mitral valve prolapse (Barlow's disease) as the underlying etiology of the endocardial lesion. Continuous antibiotics were prescribed, postoperatively. Transthoracic echocardiography at 1.5, 3, and 6 months after the onset of his illness showed no severe regurgitation, and there was no respiratory distress, fever, or lethargy during follow-up. Conclusions Although antibiotic use in IE carries a risk of septic embolism, these drugs have bactericidal and antithrombotic benefits. It is important to consider that negative blood culture and symptom resolution do not confirm complete elimination of bacteria. However, vegetation size andStaphylococcus aureus infection accurately predict embolization. It is also important to consider that bacteria can be segregated from the microbicide when embedded in platelets and fibrin. Therefore, antimicrobial therapy with concurrent antiplatelet therapy should be considered carefully.